دور أعضاء هیئة التدریس فى بناء وتنمیة مجتمع المعرفة : دراسة حالة بکلیة الآداب جامعة الامام عبد الرحمن بن فیصل - د. علیاء ابراهیم أحمد; د. نواف عبد العزیز الدخیل; د. سارة عبد الله القرنى (المجلة الدولية لعلوم المكتبات والمعلومات)
The purpose of the study is to examine the role of faculty members inbuilding and developing the knowledge society in the Library and InformationDepartment through analyzing the role played by the members of the educationalbody in producing and investing knowledge in terms of research and education,and studying the challenges facing them in building and developing knowledge.The researchers tried to achieve these goals through an analytical descriptivestudy, based on the questionnaire as a tool. And consisted of several axesaccording to the objectives of the study. The study found that there are manychallenges faced by faculty members in this field, the most important of which areadministrative burdens (96.7%) and poor quality and learning outcomescompared with learning in foreign countries (86.7%). In light of these results, thestudy suggested some recommendations, the most important of which were: thepublication of scientific research in classified journals and the preparation ofqualified human resources according to the needs of the labor market andconducting research and studies on knowledge building.